(untitled) (Orchid Academia Siraha, 2023)
The Khasa Chhetris are an integral group of the Nepali society. The Nepali language (Khaskura) is believed to have sprung from the tongues of the Khasas such as Mugali, Achhami, and mainly Sinjali or Jumli spoken in the Karnali region. This paper seeks to make the representation of the Chhetris as the direct descendants of the ancient Khasas, and to highlight their distinct traditions and customs from the historical perspective. It argues that the Khasas are the ancient settlers of western Nepal having the amalgamation of shamanic and Vedic traditions. Their matrilineal society transformed into patrilineal framework owing to the accumulation of wealth in the hands of males and the consequent idea of private property. This study would encourage the scholars to look at this issue from the perspectives or the oral narratives of the Khasa Chhetris.